The Role of Semaphorin 3A in Bone Remodeling - Li, Zhenxia; Hao, Jin; Duan, Xin; Wu, Nan; Zhou, Zongke; Yang, Fan; Li, Juan; Zhao, Zhihe; Huang, Shishu (Frontiers in Cellular Neuroscience, 2017)
Bone remodeling occurs at the bone surface throughout adult life and associates bony quantity and quality. This process is a balance between the osteoblastic bone formation and osteoclastic bone resorption, which cross-talks together. Semaphorin 3A is a membrane-associated secreted protein and regarded as a diffusible axonal chemorepellent, which has been identified in the involvement of bone resorption and formation synchronously. However, the role of Semaphorin 3A in bone homeostasis and diseases remains elusive, in particular the association to osteoblasts and osteoclasts. In this review article, we summarize recent progress of Semaphorin 3A in the bone mass, homeostasis, and diseases and discuss the novel application of nerve-based bone regeneration. This will facilitate the understanding of Semaphorin 3A in skeletal biology and shed new light on the modulation and potential treatment in the bone disorders.